Соціальний захист дітей-сиріт та дітей, позбавлених батьківського піклування : виклики та шляхи їх подолання - Шумінська, Ярина Ярославівна; Shuminska, Yaryna Yaroslavivna (Національний університет "Львівська політехніка", 2024)
Одним із найбільших викликів сучасного українського суспільства є захист прав дітей, особливо дітей-сиріт та дітей, позбавлених батьківського піклування. Відтак, головним гарантом щодо утримання цієї категорії громадян конституційно виступає держава, яка зобов’язана забезпечити всім необхідним, що відповідатиме сучасним потребам задля їх всебічного розвитку. Водночас, на думку Л. Самчук та К. Данильчук, на шляху інтеграції України до європейської спільноти повинен стояти орієнтир трансформації державної політики щодо даної категорії дітей (Самчук & Данильчук, 2022). Об'єкт дослідження: система соціального захисту дітей-сиріт та дітей, позбавлених батьківського піклування в Україні та світі. Предметом дослідження є проблемні аспекти у системі соціального захисту дітей-сиріт та дітей, позбавлених батьківського піклування в Україні та шляхи їх подолання . Мета дослідження проаналізувати основні виклики щодо функціонування системи соціального захисту дітей-сиріт та дітей, позбавлених батьківського піклування та запропонувати шляхи їх вирішення. Результати дослідження: у роботі було визначено, що соціальна підтримка дітей-сиріт та дітей, позбавлених батьківського піклування є недостатньою, що породжує необхідність її удосконалення.

One of the most significant challenges facing contemporary Ukrainian society is the protection of children’s rights, especially orphans and children deprived of parental care. Consequently, the state constitutionally acts as the primary guarantor for the well-being of this category of citizens, obligated to provide all necessary regarding that meet modern needs for their comprehensive development. At the same time, according to L. Samchuk and K. Danylchuk, Ukraine's path to European integration should be guided by the transformation of state policy concerning this category of children (Samchuk & Danylchuk, 2022). The object of the study: the system of social protection of orphans and children deprived of parental care in Ukraine and worldwide. The subject of the study is the problematic aspects within the system of social protection of orphans and children deprived of parental care in Ukraine and the ways to overcome them. The purpose of the study to analyze the main challenges regarding the functioning of the system of social protection of orphans and children deprived of parental care and to suggest the solutions. Research results: the study determined that the social support of orphans and children deprived of parental care is insufficient, which necessitates its improvement.
Social protection of orphans and children deprived of parental care: challenges and ways to overcome them
Keywords: 6.232.00.00; соціальний захист; діти-сироти; діти; позбавлені батьківського піклування; державна соціальна допомога; social protection; orphans; children deprived of parental care; state social benefit